Local Matters: Queer Scenes in 1960s Manchester, Plymouth, and Brighton. (January 2020) - Cook, Matt
Abstract: This article compares queer social scenes in the 1960s in three English towns and cities: Brighton and Plymouth on the south coast and Manchester in the northwest. It considers how queer experience in these places was affected by local identities, demographics, geographies, and socioeconomic circumstances and so demonstrates how and why the local matters to queer scenes and lives, even in the midst of wider burgeoning mass and connective cultures. A focus on London has dominated analysis of both the "Swinging Sixties" and queer lives in England; this article shows how different queer experience outside that city could be. Despite multiple resonances and connections, London's queer story cannot stand in for that of other places.